Engineering mechanical microenvironment of macrophage and its biomedical applications. (March 2018) - Li, Jing; Li, Yuhui; Gao, Bin; Qin, Chuanguang; He, Yining; Xu, Feng; Yang, Hui; Lin, Min
Macrophages are the most plastic cells in the hematopoietic system and can be widely found in almost all tissues. Recently studies have shown that mechanical cues (e.g., matrix stiffness and stress/strain) can significantly affect macrophage behaviors. Although existing reviews on the physical and mechanical cues that regulate the macrophage's phenotype are available, engineering mechanical microenvironment of macrophages in vitro as well as a comprehensive overview and prospects for their biomedical applications (e.g., tissue engineering and immunotherapy) has yet to be summarized. Thus, this review provides an overview on the existing methods for engineering mechanical microenvironment of macrophages in vitro and then a section on their biomedical applications and further perspectives are presented.